A High-Speed 84 Gb/s VSB-PAM8 VCSEL Transmitter-Based Fiber–IVLLC Integration - Yun-Chieh Wang; Hai-Han Lu; Chung-Yi Li; Pei-Hsien Chew; Yu-Bo Jheng; Wen-Shing Tsai; Xu-Hong Huang (IEEE Photonics Journal, 2018)
A high-speed 84 Gb/s vestigial sideband (VSB)–eight-level pulse amplitude modulation (PAM8) fiber-invisible laser light communication (IVLLC) integration based on vertical-cavity surface-emitting laser (VCSEL) transmitter with injection locking scheme is proposed. To the authors’ knowledge, this study is the first to realize a high-speed 84 Gb/s VSB-PAM8 VCSEL transmitter-based fiber–IVLLC integration. It is effectual to adopt an optical VSB-PAM8 signal in fiber–IVLLC integrations to suppress the linewidth of an optical signal so as to reduce the fiber dispersion. An injection locking scheme and a linear equalizer possess enhancements in frequency response, and thereby provide good transmission performances in a high-speed VSB-PAM8 fiber–IVLLC integration. Impressive bit error rate performance and clear eye diagrams are acquired in real time at a 25-km single-mode fiber operation with a 10-m free-space link. Such proposed 84 Gb/s VSB-PAM8 VCSEL transmitter-based fiber–IVLLC integration is a notable option for providing high transmission rates at optical fiber and optical wireless communications.